2021
DOI: 10.21203/rs.3.rs-867162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Vaccine Uptake Among People Living With HIV

Abstract: People living with HIV (PLWH) are at greater risk for severe COVID-19 and are a priority population for COVID-19 vaccination. As of June 15, 2021, 61.5% of PLWH in Oregon received ≥ 1 COVID-19 vaccine dose. Younger PLWH, Hispanic/Latinx PLWH and PLWH who inject drugs or reside in rural and frontier areas had low vaccine uptake while PLWH who were engaged in care, enrolled in the AIDS Drug Assistance Program, and vaccinated against influenza had high vaccine uptake. Greater advocacy, education, and care navigat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, several challenges persist in ensuring high coverage of COVID-19 vaccination among PWH. A study of COVID-19 vaccine uptake among PWH in Oregon found that as of June 2021 only about two-thirds of PWH had received the vaccine; younger PWH, Hispanic/Latinx PWH, and PWH who inject drugs or reside in rural areas had lower vaccine uptake ( 7 ). Attitudes toward vaccination also play a role in vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…However, several challenges persist in ensuring high coverage of COVID-19 vaccination among PWH. A study of COVID-19 vaccine uptake among PWH in Oregon found that as of June 2021 only about two-thirds of PWH had received the vaccine; younger PWH, Hispanic/Latinx PWH, and PWH who inject drugs or reside in rural areas had lower vaccine uptake ( 7 ). Attitudes toward vaccination also play a role in vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 vaccination among people living with HIV has been reported to be low (12). In a study carried out among PLWHV (13), it was reported that COVID-19 vaccination uptake was low and stated that PLWHV will probably not get vaccinated as a result of vaccine safety and side effects. A study carried out on the acceptance of COVID-19 vaccination in China also reported a relatively low COVID-19 vaccine acceptance rate among PLWHV compared to the general population (14).…”
Section: Introductionmentioning
confidence: 99%